The synthesis of novel pyrazole-3,4-dicarboxamidesbearing 5-amino-1,3,4-thiadiazole-2-sulfonamide moiety with effective inhibitory activity against the isoforms of human cytosolic carbonic anhydrase I and II - Mert, Samet; Alim, Zuhal; Isgor, Mehmet Mustafa; Beydemir, Şükrü; Kasimogullari, Rahmi (Academic Press Inc Elsevier Science, 2016)
A series of 1-(3-substituted-phenyl)-5-phenyl-N-3,N-4-bis(5-sulfamoyl-1,3,4-thiadiazol-2-yl)-1H-pyrazole-3,4- dicarboxamides (4-15) were synthesized. The structures of these pyrazole-sulfonamides were confirmed by FT-IR, H-1 NMR, C-13 NMR and elemental analysis methods. Human cytosolic carbonic anhydrase (CA, EC 4.2.1.1) isozymes (hCA I and II) were purified from erythrocyte cells by affinity chromatography. The inhibitory effects of newly synthesized derivatives (4-15) were investigated in vitro on esterase activities of these isozymes. The K-i values were determined as 0.119-3.999 mu M for hCA I and 0.084-0.878 mu Mfor hCA II. The results showed that the compound 6 for hCA I and the compound 11 for hCA II had the highest inhibitory effect. Beside that, the compound 8 had the lowest inhibition effect on both isozymes. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pyrazole-3,4-dicarboxylic acid; 1,3,4-Thiadiazole-2-sulfonamide; Synthesis; Antiglaucoma; Inhibition; Carbonic anhydrase